TEKNIK PENANGKARAN DAN AKTIVITAS HARIAN MAMBRUK VICTORIA (Goura Victoria Fraser, 1844) DI MEGA BIRD AND ORCHID FARM BOGOR, JAWA BARAT - Angga Prayana; Burhanuddin Masy'ud; Erna Suzanna (Media Konservasi, 2012)
Victoria crowned pigeon (Goura victoria Fraser, 1844) is one of endemic bird species in Papua, which population had decreased in the natural habitat due to hunting activities. Ex-situ conservation through captive breeding or captivity is an alternative to sustain the bird population. Observation on it’s daily activities in captivity was expected to result in good captivity technique which would enable the preservation of it’s population and restocking of the species in their natural habitat. The cage was classified a permanent maintenance cage with 40 m × 25 m × 5 m dimensions which made from wall, iron with + 5 cm in diameter, and ram wire for roof. Facilities provided in the cage were among other perch place, eating and drinking place, nesting place, and pond. The cage was regularly cleaned twice a day and sprayed with disinfectant once a month. Temperature in the cage was between 25 – 32oC with moist air ranges between 57 – 78%. The type of diseases suffered by the victoria crowned pigeon were CRD (Chronic Respiratory Disease), intestinal worms, and leg swelling. Technique of pairing, laying or hatchery setting, and native enlargement was naturally done by victoria crowned pigeon’s parent. Factors which support the success of captive breeding management in MBOF were (a) location of the cage which away far from noise and human disturbance; (b) the hygiene, safety, and care of the cage; (c) the feeding routine given every morning and evening; (d) provision of medication and vitamins on regular basis to maintain good health and prevent disease from attacking the birds in captivity; and (e) maintenance of genetic purity and avoidance of inbreeding occurenes. Type of behavior that can be used to distinguish the sex of the victoria crowned pigeon was dancing behaviour performed by male individuals. Keywords: victoria crowned pigeon, captive, daily activity, behaviour, breeding successfullt,